Urinary bladder recurrences following ureteroscopic biopsies of upper tract urothelial cancers: a multi-centre observational study with genomic assessment for clonality. Issue 1 (February 2023) - Anbarasan, Thineskrishna; Nissar, Sheikh; Turbitt, Julie; Walls, Kathryn; McLuckie, Sarah; Clark, Caroline; Bourdon, Jean-Christophe; Tracey, Joel; Bray, Susan; Shamsuddin, Atlaf; Alcorn, Jason; Jain, Sunjay; et al.
Background and aims: Urinary bladder recurrences (UBRs) after radical nephroureterectomy (RNUx) are a known challenge in patients with upper-tract urothelial cancers (UTUCs). We aim to assess factors associated with UBR and clonal-relatedness with resected UTUC. Methods: Patients who underwent RNUx for UTUC between 1998 and 2015 in five institutions were identified. Clonal relatedness between primary UTUC and subsequent UBR in a sub-cohort was assessed using next-generation sequencing. A Kaplan–Meier curve was used to assess differences in UBR between two groups (with or without ureteroscopic biopsy). Results: Of 267 patients with complete records, 73 (27.3%) had UBR during follow-up. The five-year UBR-free survival in all patients was 64.7%. The five-year UBR-free-survival was inferior in patients who underwent URS biopsy compared with patients who did not undergo ureteroscopic biopsy (49.9% vs 76.4%, p < 0.001). History of bladder tumour (HR, 95% CI; 2.94, 1.73–5.00, p < 0.001), ureteroscopic biopsy (HR, 95% CI; 2.21, 1.38–3.53, p = 0.001) and preoperative urine cytology ≥C3 (HR, 95% CI; 2.06, 1.24–3.40, p = 0.005) were independently associated with UBR. Patients with ureteroscopic biopsy (n = 3/5) showed identical mutational changes for common genes ( TP53 and FGFR3 ) between primary UTUC and subsequent UBR. Conclusions: Ureteroscopic biopsy of UTUC is a significant risk factor for UBR. Qualitative clonality assessment showed identical mutational signatures between primary UTUC and UBR.